2022
DOI: 10.3389/fpsyg.2022.890861
|View full text |Cite
|
Sign up to set email alerts
|

Learning leadership and feedback seeking behavior: Leadership that spurs feedback seeking

Abstract: Lifelong learning is crucial for professionals to continuously develop and update their knowledge and skills, and for organizations to create and sustain competitive advantage. In this regard, feedback seeking is a powerful vehicle to gain new knowledge and insights in one’s development and performance. The current research dives deeper in the concept of feedback seeking by investigating the act and use of feedback as well as multiple feedback seeking methods. Leadership as a contextual factor can affect emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Relying instead on their strategies to select relevant articles choosing to "read smart" not read everything. However, as medical knowledge is increasing exponentially (Corish, 2018) these current strategies may become more and more ineffective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relying instead on their strategies to select relevant articles choosing to "read smart" not read everything. However, as medical knowledge is increasing exponentially (Corish, 2018) these current strategies may become more and more ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…Medical professionals are facing major challenges to keep abreast of current and updated information with the rapidly growing clinical and scienti c knowledge (Prasad & Kumar, 2013). The expectation to update and maintain knowledge as a health professional is implicit in the medical eld and is paramount to provide the best care for the patient (Corish, 2018). Medical knowledge has been expanding exponentially (Corish, 2018) over the last 10 years with an explosion of health care knowledge worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Performance pressure can be considered a job demand (Adeel et al, 2023) as it involves high expectations, time pressure (Shalley and Perry-Smith, 2001) and the need to meet the required demanded output (Zhang et al, 2017). On the other hand, FSB can be viewed as a job resource (Crans et al, 2022) within the JD-R theory, which helps manage job demands. Seeking feedback allows employees to gather information about their performance, identify areas for improvement and make necessary adjustments, thereby enhancing their job performance (Zhang et al, 2022a) and reducing the adverse effects of job demands (Anseel et al, 2015).…”
Section: Igniting Work Innovationmentioning
confidence: 99%
“…The JD-R model suggests that job resources can offset the detrimental effects of job demands. In the context of the JD-R model, FSB is considered a job resource (Crans et al, 2022), and performance pressure is a job demand (Adeel et al, 2023). Employees engage in FSB because they recognize the informational value of feedback in helping them improve their performance and regulate their behavior (Katz et al, 2023).…”
Section: Hypothesis Development 21 Performance Pressure and Fsbmentioning
confidence: 99%
“…The literature on learning climate has also pointed to the interaction between individual and context, and thus to the situatedness of learning. Crans et al (2022) found that learning-related leadership is one of the fundamental building blocks of a learning climate. In their study, employees perceived their supervisors as a crucial factor in establishing an environment that fosters learning.…”
Section: Introductionmentioning
confidence: 99%